At the End of Their Rope: A Research Note on the Influence of Parental Low Self-Control and Juvenile Delinquency on Parental Exasperation - Meldrum, Ryan Charles (Youth violence and juvenile justice, 2017)
The concept of self-control has been used to account for a wide variety of outcomes, both criminal and otherwise. Recently, researchers have started investigating associations between parental self-control and family functioning. This study expands this area of research by assessing the extent to which parental low self-control and official involvement in juvenile delinquency is associated with parental exasperation among a sample of parents (N = 101) whose children have been processed through a juvenile justice assessment facility. The results indicate that parents who are lower in self-control and whose children have had more extensive involvement in officially recorded delinquency report greater exasperation regarding their children. In addition, the data indicate the effect of parental low self-control on parental exasperation is stronger at higher levels of delinquent behavior. The implications of the study and directions for future research are discussed.